Tree Richness and Carbon Storage in Developing a Tropical Evergreen Forest after Slash-And-Burn in the Lacandon Region (London Journal of Research In Science: Natural and Formal, 2024)
The objectives were to quantify tree richness and estimate carbon stored during the recovery and development of tropical evergreen forest (BTP) affected by the traditional slash and burn (RTQ) system practiced by the Lacandon-Mayan ethnic group. This research was carried out in the Lacandona region of Mexico. The aim was to determine whether the RTQ system maintains tree species richness and whether stored C is recovered.Methods. Dismantled areas were located with the RTQ system from 5, 10, and 20 years ago (BTR5, BTR10, and BTR20, respectively). To obtain tree richness, botanical collections of all tree species present in 0.1 ha plots of BTR5, BTR10, and BTR25, as well as two BTP plots (BTP1 and BTP2, respectively) were carried out. In each plot, height, diameter at breast height, and number of individuals of each tree species were recorded. To estimate the stored C, the equation proposed by Chave et al., (2005) was used, which relates the DAP and the density of the wood of each species.Results. A tree richness of 71 species was obtained in 0.1 ha. In BTP1, 47 species were recorded and in BTP2, 38 species were recorded. The number of species increased (20, 17, and 39 species) according to the recovery age of the BTR (5, 10, and 20 years respectively), so the rest period is adequate for the recovery of tree richness. The accumulation of C in the trees showed that the RTQ system must modify the recovery or rotation age since the carbon stored at 5, 10, and 20 years was 29, 35, and 74 Mg C ha-1 respectively, while in BTP1 and BTP2 they were 478 and 512 Mg C ha-1 respectively. The polynomial model obtained indicates rest periods between 40 and 50 years to recover the C stored in the mature BTP.
Keywords: small-sized sprayer; sprayer; spray angle; field boom; transverse vibrations; spray uniformity; nomogram.; Regeneration rainforest; Environmental services; Species richness; Biodiversity; and Tropical rainforest.